2021
DOI: 10.3390/cancers13153859
|View full text |Cite
|
Sign up to set email alerts
|

Superficially Invasive Vulvar Squamous Cell Carcinoma: A 37-Year-Long Experience of a Tertiary Referral Center

Abstract: Superficially, invasive vulvar squamous cell carcinoma (SISCCA) (FIGO stage IA) is a rare subset of vulvar cancer defined as a single lesion measuring ≤2 cm with a depth of invasion of ≤1.0 mm. This is a retrospective study performed on 48 patients with SISCCA, surgically treated between 1981 and 2018 at the S. Anna Hospital, University of Turin, to evaluate pathological characteristics and prognosis of these tumors. Ten patients (21%) recurred: seven (14%) as SISCCA and three (7%) as deeply invasive carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Strikingly, most of these tumours recurred despite being at initial FIGO stage at diagnosis and with low rates of lymph node involvement, factors usually associated with improved prognosis. 27 Curiously, in a series of patients with superficially invasive VSCC, Preti et al 28 describe a higher recurrence rate in smaller tumours; the authors hypothesise that the potential presence of microscopic satellite lesions not clinically visible could be the cause of this observation. Of note, basaloid histology, which was frequent in tumours with HSIL-like adjacent lesion, has been previously associated with aggressive clinical behaviour in other cancer types, [29][30][31] especially in HPV-negative head and neck squamous cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, most of these tumours recurred despite being at initial FIGO stage at diagnosis and with low rates of lymph node involvement, factors usually associated with improved prognosis. 27 Curiously, in a series of patients with superficially invasive VSCC, Preti et al 28 describe a higher recurrence rate in smaller tumours; the authors hypothesise that the potential presence of microscopic satellite lesions not clinically visible could be the cause of this observation. Of note, basaloid histology, which was frequent in tumours with HSIL-like adjacent lesion, has been previously associated with aggressive clinical behaviour in other cancer types, [29][30][31] especially in HPV-negative head and neck squamous cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, most of these tumours recurred despite being at initial FIGO stage at diagnosis and with low rates of lymph node involvement, factors usually associated with improved prognosis 27 . Curiously, in a series of patients with superficially invasive VSCC, Preti et al 28 . describe a higher recurrence rate in smaller tumours; the authors hypothesise that the potential presence of microscopic satellite lesions not clinically visible could be the cause of this observation.…”
Section: Discussionmentioning
confidence: 99%
“…W omen have a one in 232-333 chance of developing vulvar cancer (VC) during their lifetime, and the cancer is derived from 2 pathways: vulvar high-grade squamous intraepithelial lesion (HSIL) associated with human papillomavirus (HPV) infection, and differentiated vulvar intraepithelial neoplasia (dVIN) associated with vulvar dermatosis, the latter being the cause of 75% of the cases. [1][2][3][4][5][6] Vulvar HSIL is commonly more frequent than dVIN. The latter represents less than 10% of all VIN diagnosis, 7 but the risk of progression to invasion is much higher for dVIN.…”
mentioning
confidence: 99%
“…lichen sclerosis and vulvar intraepithelial neoplasia). [20][21][22] Some demonstrated that recurrence might be associated with close surgical margins and relatively large tumor size, and therefore advocated for a more aggressive surgical approach to those apparently low-risk cases. 23 In the current study, the risk of nodal metastases was approximately 8% in patients with apparent "low-" risk tumors with tumor grade 1 and tumor size ≤2 cm.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 99%